2017
DOI: 10.1186/s12885-017-3806-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 5–year overall survival in cervical cancer patients treated with radical hysterectomy using computational intelligence methods

Abstract: BackgroundComputational intelligence methods, including non-linear classification algorithms, can be used in medical research and practice as a decision making tool. This study aimed to evaluate the usefulness of artificial intelligence models for 5–year overall survival prediction in patients with cervical cancer treated by radical hysterectomy.MethodsThe data set was collected from 102 patients with cervical cancer FIGO stage IA2-IIB, that underwent primary surgical treatment. Twenty-three demographic, tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 76 publications
1
47
0
2
Order By: Relevance
“…Previous survival analysis studies using machine learning involved the use of support vector machine-based prediction models (sensitivity = 0.89; specificity = 0.73) or decision support systems (C-index = 0.84 with an accuracy of 86%) to predict breast cancer recurrence 9,10 , and probabilistic neural networks to predict cervical cancer recurrence (sensitivity = 0.975; accuracy = 0.892) 11 . In their research on lung cancer, Lynch et al compared various supervised machine learning classification techniques using the Surveillance, Epidemiology, and End Results (SEER) database and showed that the models in which the gradient boosting machine was utilized with the root-mean-squared error (RMSE) were the most accurate 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous survival analysis studies using machine learning involved the use of support vector machine-based prediction models (sensitivity = 0.89; specificity = 0.73) or decision support systems (C-index = 0.84 with an accuracy of 86%) to predict breast cancer recurrence 9,10 , and probabilistic neural networks to predict cervical cancer recurrence (sensitivity = 0.975; accuracy = 0.892) 11 . In their research on lung cancer, Lynch et al compared various supervised machine learning classification techniques using the Surveillance, Epidemiology, and End Results (SEER) database and showed that the models in which the gradient boosting machine was utilized with the root-mean-squared error (RMSE) were the most accurate 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Another consequent limitation of the retrospective de-sign is the lack of adequate power to calculate a sample size at which the outcomes could be statistically reliable. Finally, we applied a Cox proportional hazards regression to investigate the impact of patient/tumor characteristics on survival, while a novel model, based on deep-learning neural network models, has proven to be more effective in predicting patients' survival; 42,43 the use of such a model in our setting may be recommended to improve treatment decision-making and outcomes by providing more accurate predictions.…”
Section: Predictormentioning
confidence: 99%
“…The AUROC curve is a summary measure of performance that indicates whether on average a true positive is ranked higher than a false positive rate or not. AUROC curve was also used for evaluation of different techniques [18,27] in biomedical data mining. There are 50% of cervical cancer identification in females age (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and around 20% diagnosed more than 65 years old as well as around 15% of between the age of (20 -30).…”
Section: Resultsmentioning
confidence: 99%
“…Positive results were obtained in most experiments as compared to other methods. Bogdan Obrzut et al [27] utilized computational intelligence methods for prediction for cervical cancer patients. The probabilistic neural network (PNN) was a very efficient method for predicting overall survival in cervical cancer patients treated with radical hysterectomy.…”
Section: Introductionmentioning
confidence: 99%